The purpose of this study is to analyze the factors that influence Organizational Citizenship Behavior (OCB) of employees at PT Mas Arya Indonesia in Semarang. The motivation of this study is from the observation that there is currently a shortage in OCB - Qristin Violinda; Heri Prabowo; Nasrul Syahputra (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to analyze the factors that influence Organizational Citizenship Behavior (OCB) of employees at PT Mas Arya Indonesia in Semarang. The motivation of this study is from the observation that there is currently a shortage in OCB among employees in the industrial sector. This study specifically targeted employees of PT. Mas Arya Indonesia, with a sample size consisting of 92 people. This research utilizes Purposive Sampling technique, which is a type of Non-Probability Sampling methodology. This method entails selecting participants based on certain factors or criteria. The data collection procedure requires distributing questionnaires that assess 38 factors using a Likert Scale. The data analysis technique used is Partial Least Square- Structural Equation Model (PLS-SEM). The test results showed strong and statistically significant relationships between organizational justice, organizational commitment, organizational support, and job satisfaction. In addition, it is important to recognize that factors such as organizational justice, organizational commitment, organizational support, and job satisfaction have a significant and positive impact on OCB. Job satisfaction serves as a mediator in the relationship between organizational justice, organizational commitment, and organizational support for OCB.